Karakteristik Sosial-Ekonomi Keluarga Tukang Ojek Perahu Laut di Kepulauan Selayar - Muh. Ryan Alfadly D; Sukri Nyompa; Sulaiman Zhiddiq; Ichsan Invanni; Hasriyanti Hasriyanti (UNIVERSITAS NEGERI MAKASSAR, 2023)
AbstractThis study aims to find out (1) knowing the social life of the family of a sea boat motorcycle taxi driver in Bontosunggu Village, (2) knowing the economic life of a sea boat motorcycle taxi driver family in Bontosunggu Village. This research was conducted in Bontosunggu Village, Bontoharu District, Selayar Islands Regency. The type of research used is quantitative with descriptive analysis. With data collection techniques using a questionnaire. sampling technique saturated against 23 respondents. The data was collected by means of observation, questionnaires, and documentation techniques, then the results of the field findings were analyzed by reducing the data, presenting the data and drawing conclusions. The results of this study: (1) the social life of the family of sea boat motorcycle taxi drivers began to realize the importance of education as seen by the majority of family members having a minimum of high school education. The majority of families of marine boat motorcycle taxi drivers have entered the age of productivity so that they can help meet family needs. (2) the economic life of the family of a boat ojek driver comes from the income obtained from various kinds of work carried out by family members such as a sea boat ojek driver for the head of the family and for his son as a laborer, farmer and entrepreneur. They also do various kinds of side jobs such as fishermen, farmers, and entrepreneurs. The income obtained also varies from IDR 300,000 to 3,000,000 both side and main income. AbstrakPenelitian ini bertujuan untuk mengetahui (1) mengetahui kehidupan sosial keluarga tukang ojek perahu laut di Desa Bontosunggu, (2) mengetahui kehidupan ekonomi keluarga tukang ojek perahu laut di Desa Bontosunggu. Penelitian ini dilakukan di Desa Bontosunggu Kecamatan Bontoharu Kabupaten Kepulauan Selayar. Jenis penelitian yang digunakan adalah kuantitatif dengan analisis deskriptif. Dengan teknik pengumpulan data menggunakan angket. teknik pengambilan sampling jenuh terhadap 23 responden. Pengumpulan data dilakukan dengan teknik observasi, angket, dan dokumentasi, kemudain hasil temuan lapangan tersebut dianalisis dengan mereduksi data, menyajikan data dan menarik kesimpulan. Adapun hasil dari penelitian ini: (1) kehidupan sosial keluarga tukang ojek perahu laut mulai sadar tentang pentingnya pendidikan dilihat dengan mayoritas anggota keluarga berpendidikan minimal SLTA. Mayoritas keluarga tukang ojek perahu laut telah masuk usia produktivitas sehingga dapat membantu memenuhi kebutuhan keluarga. (2) kehidupan ekonomi keluarga tukang ojek perahu berasal dari pendapatan yang diperoleh dari berbagai macam pekerjaan yang dilakukan anggota keluarga seperti tukang ojek perahu laut bagi kepala keluarga dan bagi anak laki-lakinya sebagai buruh, petani dan wirausaha. Mereka juga melakukan berbagai macam pekerjaan sampingan seperti nelayan, petani, dan wirausaha. Pendapatan yang didapatkan juga bervariasi mulai dari Rp300.000 hingga 3.000.000 baik itu pendapatan sampingan maupun pokok.